1999
DOI: 10.1055/s-2007-1013117
|View full text |Cite
|
Sign up to set email alerts
|

Action of Aprotinin in Myocardial Ischemia - an Investigation Using a Plasma-Free Model

Abstract: The findings demonstrate that aprotinin in a moderate dose is effective in reducing postischemic troponin release in a non-blood perfused system. Measurement of myocardial high-energy phosphates after aprotinin use was performed for the first time and indicates that not a reduction in severity of direct myocardial ischemic intensity but a beneficial action on processes causing release of troponin is the mode of action of this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…21 In rodent models of I/R, it has been shown that aprotinin, when administered 5 min before reperfusion (10,000-20,000 KIU/kg), reduces leucocyte infiltration into the myocardium and myocardial injury as measured by CK release. 22 A similar study was done by Hoffmeister et al 23 in isolated Langendorff preparations in which they showed that aprotinin improves the recovery of myocardial contractility and decreases the release of troponin T (TnT), relative to saline.…”
Section: Discussionmentioning
confidence: 76%
“…21 In rodent models of I/R, it has been shown that aprotinin, when administered 5 min before reperfusion (10,000-20,000 KIU/kg), reduces leucocyte infiltration into the myocardium and myocardial injury as measured by CK release. 22 A similar study was done by Hoffmeister et al 23 in isolated Langendorff preparations in which they showed that aprotinin improves the recovery of myocardial contractility and decreases the release of troponin T (TnT), relative to saline.…”
Section: Discussionmentioning
confidence: 76%
“…In a canine heart ischemia/reperfusion model, McCarthy and coworkers showed that aprotinin‐treated animals had improved systolic function, as measured by greater percent systolic shortening 23 . Hoffmeister and coworkers showed in an isolated nonblood perfused ischemia/reperfusion model that pretreatment with IV aprotinin (10,000 KIU) prior to 30 minutes of global ischemia resulted in significantly less Troponin T release 24 . This suggests that not only is aprotinin effective in the absence of cardiopulmonary bypass, but it may also work directly on the myocardium, and is not dependent on plasma kallikrein‐kinin or fibrinolytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There are data available that indicate that the decreased Ca 21 responsiveness of stunned myocardium is due to intrinsic alterations of the myo®laments. This could account for the fact that even in the buffer perfused isolated rat heart model, aprotinin was able to reduce the extent of myocardial damage [24]. Ca 21 activated protease activity, such as calpain I, decreases the Ca 21 responsiveness of the cardiac myo®laments by reperfusion induced Ca 21 -overload [25].…”
Section: Discussionmentioning
confidence: 99%